1、 1 1.3 b eq f(3,2 ) C(s)= =eq f(3,2 )CO2 (g) 2Fe(s) H 234 .1 kJ mol 1 C(s) O2(g )= CO2 (g) H 393.5 kJ 1 2 5 7 9 10 3 4 6 8 11 12 298 K 100 kPa eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2H2O(g)=O2(g) 2H2(g) H1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol
2、1 C(s) O2(g)=CO2(g) H 393.5 kJ 2(g) H2(g)=2HCl(g) H2 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2(g) 2H2O(g)=4HCl(g) O2(g) H3 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H3 H1 H2 ( ) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 2
3、34.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ A H3 H1 H2 B H3 H1 H2 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ C H3 H1 H2 D H3 H1 H2 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H1 H2 H3 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 23
4、4.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ A eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2 H2O H2 ( ) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 k
5、J A H1 H2 H3 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ B H H a 1 O=O b 1 1 mol H O H1 a b) kJ eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ C H2 H3 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 3
6、93.5 kJ D H2 kJ eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H1 H2 H3) A H2O(g)=H2(g) 1 2 O2(g) H H1 H H O=O a b 2kJ O H H1 a b 2 2kJ B 1 mol H2O(g) 1 mol H2O(l) H2 kJ D eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2 C eq f(3,
7、2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 3 1MOH c(OH ) 4 1 pH 10 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2MOH(aq) H2SO4(aq)=M2SO4(aq) 2H2O(l) H1 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.
8、5 kJ H (aq) OH (aq) H2O(l) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H2 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ MOH H ( ) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ A 1B 1 eq f(
9、3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ C 1D 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ MOH MOH(aq) H (aq)=M (aq) H2O(l) H 1 H (aq) OH (aq)=H2O(l) H 1 (aq) OH (aq) H 1 B eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1
10、 C(s) O2(g)=CO2(g) H 393.5 kJ B eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 4 X Y Z W ( ) H H1 H2 X Y ( ) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 3
11、93.5 kJ SO2 3 Al(OH)3 2=CH2 CH3CH3 3OH HCHO eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ A B eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ C D eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ X
12、S Y SO2 W O2 Z SO3 S SO3 X AlCl3 Y Al(OH)3 W NaOH Z NaAlO2 AlCl3 3NaOH=Al(OH)3 3NaCl Al(OH)3 NaOH=NaAlO2 2H2O AlCl3 4NaOH=NaAlO2 3NaCl 2H2O H H1 H2 X CH2=CH2 Y CH3CH3 W H2 Z X CH3OH Y HCHO W O2 Z HCOOH 2CH3OH O2 2H2O,2HCHO O2 CH3OH O2 H2O H H1 H2 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1
13、C(s) O2(g)=CO2(g) H 393.5 kJ C eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 5 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2H2(g) 5 2 O2(g)=2CO2(g) H2 H1 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g)
14、 H 393.5 kJ 3 O2(g)=CO2 H2 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2(g) 1 2 O2(g)=H2O(l) H3 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H2(g)=C2H2(g) H ( ) eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2
15、(g)=CO2(g) H 393.5 kJ A 1B 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ C 1D 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ eq f(3,2)C(s)=eq f
16、(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ H2 H3 H1 H 1 ) ( 1 ) ( 1 ) 1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ A eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 6 2H (aq)=Cu 2 (aq) H2(g) H1 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ 2O2(l)=2H2O(l) O2(g) H2 eq f(3,2)C(s)=eq f(3,2)CO2(g) 2Fe(s) H 234.1 kJmol 1 C(s) O2(g)=CO2(g) H 393.5 kJ